Obesity Drives an Oral Microbiota Signature of Female Patients with Periodontitis: A Pilot Study - Charlotte Thomas; Matthieu Minty; Thibault Canceill; Pascale Loubières; Vincent Azalbert; François Tercé; Camille Champion; Rémy Burcelin; Pierre Barthet; Sara Laurencin-Dalicieux; Vincent Blasco-Baque (Diagnostics, 2021)
The aim of this study was to analyze the link between oral microbiota and obesity in humans. We conducted a pilot study including 19 subjects with periodontitis divided into two groups: normo-weighted subjects (NWS) with a body mass index (BMI) between 20 and 25 (n = 9) and obese subjects (OS) with a BMI > 30 (n = 10). Obesity was associated with a poor oral health status characterized by an increased number of missing teeth and a higher score of periodontal-support loss associated with dysbiotic oral microbiota (39.45 ± 3.74 vs. 26.41 ± 11.21, p = 0.03 for the Chao 1 index). Oral microbiota taxonomic analysis showed that the abundance of the Capnocytophaga genus was higher (2.47% ± 3.02 vs. 0.27% ± 0.29, p = 0.04) in OS compared to NWS. Obese females (OF) were characterized by an increase in the Streptococcus genus (34.12% ± 14.29 vs. 10.55% ± 10.42, p = 0.05) compared to obese males (OM), where the Neisseria genus was increased (5.75% ± 5.03 vs. 58.05% ± 30.64, p = 0.008). These first data suggest that sex/gender is determinant in the link between oral dysbiotic microbiota and obesity in patients with periodontitis. Our results could lead to recommendations concerning therapeutic strategies for obese patients with periodontitis following the sex/gender.